Oct4 Methylation-Mediated Silencing As an Epigenetic Barrier Preventing Müller Glia Dedifferentiation in a Murine Model of Retinal Injury - Reyes-Aguirre, Luis I.; Lamas, Monica (Frontiers in Neuroscience, 2016)
Müller glia (MG) is the most abundant glial type in the vertebrate retina. Among its many functions, it is capable of responding to injury by dedifferentiating, proliferating and differentiating into every cell types lost to damage. This regenerative ability is notoriously absent in mammals. We have previously reported that cultured mammalian MG undergoes a partial dedifferentiation, but fails to fully acquire a progenitor phenotype and differentiate into neurons. This might be explained by a mnemonic mechanism comprised by epigenetic traits, such as DNA methylation. To achieve a better understanding of this epigenetic memory, we studied the expression of pluripotency-associated genes, such as Oct4, Nanog and Lin28, which have been reported as necessary for regeneration in fish, at early times after NMDA-induced retinal injury in a mouse experimental model. We found that although Oct4 is expressed rapidly after damage (4 hpi), it is silenced at 24 hpi. This correlates with a significant decrease in the DNA methyltransferase Dnmt3b expression, which returns to basal levels at 24 hpi. By MS-PCR, we observed a decrease in Oct4 methylation levels at 4 and 12 hpi, before returning to a fully methylated state at 24 hpi. To demonstrate that these changes are restricted to MG, we separated these cells using a GLAST antibody coupled with magnetic beads. Finally, intravitreous administration of the DNA-methyltransferase inhibitor SGI-1027 induced Oct4 expression at 24 hpi in MG. Our results suggest that mammalian MG injury-induced dedifferentiation could be restricted by DNA methylation, which rapidly silences Oct4 expression, preventing multipotency acquisition.